Can wine quality be predicted by small volatile compounds? A study based on performance of wine show entries and their volatile profiles. (18th September 2022) - Luo, Jiaqiang; Zhang, Pangzhen; Loo, Yit Tao; Ma, Jiayu; Wu, Shanshan; Marriott, Philip J.; Howell, Kate
Abstract: It is widely recognized that wine aroma critically influences wine quality, yet the extent to which volatile compound composition in wine determines wine quality has proven difficult to define, beyond the negative influence of taint compounds. While some relationships between concentration of volatile aroma compounds and wine quality have been made, this has been usually based on single molecules, in laboratory wines and without reference to experienced wine panels. Here, we collected and analysed 157 commercial Shiraz wines from a competitive show over 2 years. We found significant ( P  < .05) correlations between specific volatiles and the panel's wine quality scores. However, these correlations were not always consistent between years. We could not explain medals given to wine entries solely based on multivariate analysis of their composite volatile composition. Here, we suggest that aroma determination in judging wine quality does not completely explain the assessment of wine, and appearance (colour, clarity) and taste may be more influential factors. There are considerable practical difficulties in establishing a convincing wine quality prediction model based on analysis of volatile compounds alone. Abstract : Wine shows are recognized as a method for wine quality assessment by the global wine industry. This study investigates the possibility of explaining medals given in wine shows by the occurrence and abundance of headspace volatile profiles of wine.